A esmola e a rede de proteção : um estudo de instituições assistenciais para as pessoas que vivem nas ruas - Melo, Natália Maximo e (Universidade Federal de São Carlos, 2016)
Innumerous City Halls all over Brazil promote periodic campaigns using slogans such as: “Do not spare money: give citizenship and future”, or “Do not spare money. Refer to Assistance services”. Based on these assumptions, we intend to investigate the strategies followed by São Carlos (SP) government in order to manage this population and to keep these people under institutional control. São Carlos was one of the first non-metropolitan cities where homeless population issues were articulated to the establishment of Municipal-Level Public Policies. Having these aspects in mind, some research questions can emerge: Which is this population that is considered as a target by the government? What is the Institutions’ role in the management of homeless people? Methodologically, we observe some practices promoted by the institutions which manage this population, analyzing them through the theories created by Das and Poole in their work State and its Margins: comparative ethnographies (2008). The margins, in our study, cover, thus, Governmental and Non-governmental Organizations; they also cover these organizations’ employees, target public and individuals who are helped by their assistance. Our research mainly investigates the Centro POP (a National Social Assistance Policy Unit administrated by the City Hall) as well as the Hostel (a philanthropic institution which supports and donates tickets to travellers) and the Religious Community (a volunteer work that assists homeless people). To develop this research, we collected in two newspapers from São Carlos dated from 2007 to 2013, as well as the Centro POP’s documentation. We interviewed several people who work at Centro POP and observed their routine as well. Our investigation also based its analysis on the verification of volunteer work promoted by a religious group on a City Center Square and on visits to Assistance Institutions, such as a Hostel and a Religious Community (House of Prayer), related to charity and shelter. We verify these data under Foucault’s (1992, 1999, 2006, 2008) perspectives. According to them, power permeates all kinds of relationships, shaping a microphysics which combines technology and power mechanisms to develop a population that may be managed, articulating some disciplines which, in turn, dominate individuals’ bodies and souls. The results show that a homeless population local Policy may be considered as a device, in which homeless people are connected to social representation, to institutional rules, to philanthropic and state institutions, their specialized professionals, according to a labyrinth of population management.

Dans de nombreuses villes du Brésil, des campagnes publicitaires périodiques utilisent des slogans interpelant les gens en ces termes: «Ne faites pas l’aumône, donnez de la citoyenneté» ou encore «Ne donnez pas d’argent par charité. Reportez-vous à nos services». À partir de cette contatation, une enquête a été ménée à São Carlos-SP, où la question de la population vivant dans la rue a articulé la mise en place des politiques publiques au niveau municipal. L'objectif est comprendre la façon dont le gouvernement cherche à gérer cette population en la soummetant à la maîtrise des cadres institutionnels. Puis, de nombreuses questions de recherche peuvent être posées: quelle est cette population considérée la cible de la gestion? Quelle est la place des institutions d'aide sociale dans le domaine de la gestion d'une population de personnes qui vivent dans la rue? Afin de prendre l'observation des pratiques inscrites aux formes institutionnelles gestionnaires, je me suis proposée à une ethnographie des marges d'État – selon la perspective de Das et Poole (2008). La marge, dans cette étude, couvrira les institutions de l'Etat et aussi celles non-gouvernamentales. L'enquête porte notamment sur le Centro POP – l'établissement de la Politique Nationale de l'Assistance Sociale administré par la Mairie -, également sur le Centre d'hébergement – institution philanthropique d'abri – sur le travail bénévole et, finalement, la Maison de Prière – une Communauté Religieuse qui fournissent des soins aux personnes vivant à la rue. Pour développer la recherche, premièremente, une collecte des articles a été prise dans deux journaux de São Carlos-SP, entre 2007 à 2013; en suite, des documents officiels du Centro POP ont été recuillis, aussi des entretiens avec les travailleurs des institutions et l'observation de la routine au Centro POP ont été ménées. Pour accomplir le terrain d'enquête, des observations du travail bénévole et des visites aux autres institutions ont été également prises. L'analyse est basée sur la théorie de Foucault (1992, 1999, 2006, 2008), dans laquelle le pouvoir imprègne toutes les relations et met en forme une microphysique dont le tissage de la technologie de pouvoir et ses mécanismes crée une population à gérer conformément à certaines disciplines du corps et de l'âmes des individus. À la fin, la politique pour la population vivant dans la rue est comprise en tant qu'un dispositif dans lequel les assistés sont enchevêtrés, soit au sein des institutions philanthropiques soit de l'Etat, à des représentations sociales, règles institutionnelles, en façonnant un labyrinthe de gestion de la population.
Sparing money and social protection network : a research about social assistance institutions for homeless people
L’aumône et le réseau de protection : une étude des institutions destinés aux personnes vivant dans la rue
Keywords: Assistência social; Instituições; Gestão da população; Pessoas vivendo nas ruas; Social assistance; Institutions; Population management; Homeless people; Assistance sociale; Gestion de la population; Personnes vivant à la rue; CIENCIAS HUMANAS::SOCIOLOGIA